Rationale of a lower dexamethasone dose in prenatal congenital adrenal hyperplasia therapy based on pharmacokinetic modelling. Issue 3 (3rd August 2021) - Stachanow, Viktoria; Neumann, Uta; Blankenstein, Oliver; Fuhr, Uwe; Huisinga, Wilhelm; Michelet, Robin; Reisch, Nicole; Kloft, Charlotte
Abstract : Context: Prenatal dexamethasone therapy is used in female foetuses with congenital adrenal hyperplasia to suppress androgen excess and prevent virilisation of the external genitalia. The traditional dexamethasone dose of 20 µg/kg/day has been used since decades without examination in clinical trials and is thus still considered experimental. Objective: As the traditional dexamethasone dose potentially causes adverse effects in treated mothers and foetuses, we aimed to provide a rationale of a reduced dexamethasone dose in prenatal congenital adrenal hyperplasia therapy based on a pharmacokinetics-based modelling and simulation framework. Methods: Based on a published dexamethasone dataset, a nonlinear mixed-effects model was developed describing maternal dexamethasone pharmacokinetics. In stochastic simulations ( n = 1000), a typical pregnant population ( n = 124) was split into two dosing arms receiving either the traditional 20 µg/kg/day dexamethasone dose or reduced doses between 5 and 10 µg/kg/day. Target maternal dexamethasone concentrations, identified from the literature, served as a threshold to be exceeded by 90% of mothers at a steady state to ensure foetal hypothalamic-pituitary-adrenal axis suppression. Results: A two-compartment dexamethasone pharmacokinetic model was developed and subsequently evaluated to be fit for purpose. The simulations, including a sensitivity analysis regarding the assumed foetal:maternal dexamethasone concentration ratio, resulted in 7.5 µg/kg/day to be the minimum effective dose and thus our suggested dose. Conclusions: We conclude that the traditional dexamethasone dose is three-fold higher than needed, possibly causing harm in treated foetuses and mothers. The clinical relevance and appropriateness of our recommended dose should be tested in a prospective clinical trial.